Episodic Seafloor Hydrothermal Alteration as a Source of Stable Remagnetizations in Archean Volcanic Rocks - A. R. Brenner; R. R. Fu; A. J. Brown; E. B. Hodgin; D. T. Flannery; Mark D. Schmitz (Geochemistry, Geophysics, Geosystems)
Abstract Interpreting the paleomagnetic records of altered rocks, especially those from Earth's earliest history, is complicated by metamorphic overprints and recrystallization of ferromagnetic minerals. However, these records may be as valuable as a primary signal if the timing and mechanism of alteration‐related remagnetizations can be ascertained. We illustrate the success of this approach in the case of seafloor hydrothermal alteration by integrating simple rock magnetic and magnetic microscopy data with petrography, hyperspectral imagery, aeromagnetic surveys, field mapping, and geochronology of Paleoarchean basalts from North Pole Dome located in the East Pilbara Craton, Western Australia. We identify 12 hydrothermal episodes during the deposition of the stratigraphy between ∼3490 and 3350 Ma. These episodes produced stratabound zones of hydrothermal alteration with predictable facies successions of mineral assemblages reflecting sub‐seafloor gradients in fluid temperature, pH, composition, and water/rock ratios. Rock magnetic data and magnetic microscopy pinpoint the secondary ferromagnetic minerals within each alteration assemblage, revealing a specific single‐domain magnetite population within leucoxenes (titanite and anatase after primary titanomagnetites) that always accompanies low‐water/rock alteration in fluids buffered to pH equilibrium with the host basalts. Highly uniform magnetic properties indicate that once formed, these magnetites remain unchanged upon further exposure to rock buffered fluids, stabilizing them against later alteration events and making them durable paleofield recorders. The altered basalts hosting this magnetite have unique and consistent appearances, mineralogy, IR absorption features, aeromagnetic signatures, and magnetic properties across all hydrothermal systems studied here, highlighting how integrating these data sets can identify and interpret this alteration style in future paleomagnetic investigations.